(untitled) (Indian Journal of Child Health, 2020)
Background: The neonatal unit equipment generates noise which is detrimental to neonatal physiological homeostasis and development. The incubator is one such essential component of modern neonatal care which, on the one hand, provides a low noise environment and also intrinsically generates noise. Objectives: The objectives of the study were to test the hypothesis that the neonatal incubator provided a better acoustic environment with lesser noise levels than the external environment. Materials and Methods: A prospective observational study was done in a Level III neonatal unit for 4 months from April 15, 2016, to August 15, 2016. Baseline noise levels of the various equipment inside a working incubator were recorded using a sound level meter. Subsequently, hourly noise levels in the neonatal intensive care unit (NICU) and inside the Giraffe Omnibed Incubator were recorded simultaneously as equivalent Continuous Sound Pressure Level as loudness equivalent. Two digital sound level meters were used. Noise levels inside and outside the incubators were used as a grouping variable. Chi-square test was used for categorical variables and independent t-test for continuous variables. All tests were two tailed and p<0.05 was considered statistically significant. Results: The noise levels recorded both inside the incubator and the NICU were >58 dbA for most times of the day. The noise levels inside the incubator were significantly less (p<0.05) than the outside. Conclusion: The statistically significant noise reduction inside the incubator provides a better acoustic environment for neonates.